The Effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Asset (ROA) on Profit Growth at PT Industri Jamu and Pharmacy Sido Muncul TBK for the 2013-2024 Period - Zahra Qurana Sabila,; Akbar, Akhmad (Jurnal Indonesia Sosial Sains, 2025)
In increasingly fierce business competition, profit growth is a key indicator of company performance, influenced by various financial factors. This study aims to examine and analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Asset (ROA) on profit growth at PT Industri Jamu Dan Pharmacy Sido Muncul Tbk for the 2013–2024 PERIOD. The research method used is a quantitative approach, with secondary data obtained from the company’s financial statements. The study results indicate that the significance value of the Current Ratio is 0.817 > 0.05, and the calculated t-value is less than the t-table value (0.240 < 1.859), leading to the conclusion that the Current Ratio partially has no significant effect on Profit Growth. The Debt to Equity Ratio also shows no significant partial effect on Profit Growth, with a significance value of 0.790 > 0.05 and a calculated t-value less than the t-table (0.275 < 1.859). In contrast, the Return on Asset reveals a significance value of 0.040 < 0.05 and a calculated t-value greater than the t-table (2.445 > 1.859), indicating that Return on Asset partially has a positive and significant effect on Profit Growth. Furthermore, the combined values of Current Ratio, Debt to Equity Ratio, and Return on Asset yield a significance value of 0.037 < 0.05 and an F-calculated value greater than the F-table (4.610 > 4.07). This demonstrates that, simultaneously, these three variables have a positive and significant effect on Profit Growth.